Intelligent systems and machine learning for industry : advancements, challenges and practices - Anisha, P. R. (London, CRC Press, 2023)
"The text discusses models related to smart automation in the manufacturing processes and early warning detection systems using machine intelligence. It will serve as an ideal reference text for graduate students and academic researchers in diverse engineering fields such as electrical, electronics and communication, computer, and information technology"--
Includes bibliographical references and index.
Keywords: Manufacturing processes; Machine learning; Medical technology; Agricultural processing; Environmental engineering